Impact of Job Stress, Psychological Well-Being, and Employee Training on Job Performance - Thida Cho Lwin; Harif Amali Rivai; Harif Amali Rivai (AMAR (Andalas Management Review), 2025)
Background – Europe & Asia Beverages Co., Ltd. is a top beverage manufacturer in Myanmar, offering soft drinks, energy drinks, and bottled water. As the industry grows, employees face rising job stress due to production demands and quality control measures. Psychological well-being and training are crucial for improving performance, yet often overlooked. This study examines how these factors impact employee outcomes at Europe & Asia Beverages Co., Ltd.